Sustainable Competitive Advantage for SMEs: Maintaining Competitiveness Amidst Increasingly Fierce Competition - Surapto, Deni; Handayani, Milcha (Syntax Corporation, 2025)
This quantitative study examines the development of competitive strategies for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, focusing on the influence of various strategies on competitive performance. This study evaluates the effectiveness of five main strategies: Cost Leadership, Differentiation,. Sample data were collected from 265 MSME respondents in Papua through a structured questionnaire that was analyzed using the Amos Structural Equation Model (SEM) to determine the relationship between these strategies and competitive performance. The results show that Cost leadership has a significant effect on overall Competitive Performance, as well as Differentiation strategy has a significant effect on Competitive Performance, thus providing insight into how MSMEs can optimize their strategic approach to increase growth and position in the market. This study emphasizes the importance of strategic management in strengthening the resilience of MSMEs, especially in the face of increasingly fierce competition and technological advances.